Deuterium Markers in CdS and Zn(O, S) Buffer Layers Deposited by Solution Growth for Cu(In, Ga)Se2 Thin‐Film Solar Cells. Issue 12 (20th October 2017) - Witte, Wolfram; De Souza, Roger A.; Martin, Manfred; Eicke, Axel; Hariskos, Dimitrios
Abstract : This contribution describes an easy and cheap approach to introduce deuterium (D) as an isotopic marker into the commonly used buffer layer materials CdS and Zn(O, S) for Cu(In, Ga)Se2 (CIGS) thin‐film solar cells. D was successfully incorporated during the growth of Zn(O, S) and CdS buffer layers by chemical bath deposition (CBD) with D2 O. CIGS solar cells prepared with D‐containing buffers grown by CBD exhibit power conversion efficiencies above 16%, that is, the D content has no detrimental effect on the performance or other solar cell parameters of the devices. With depth profiles obtained by time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) we clearly detect the intentionally incorporated D within the solution‐grown Zn(O, S) buffer. Assuming that D is present as OD, we compare the amount of OD within the Zn(O, S) layer with the amount of OH on the surface of the subsequent sputtered (Zn, Mg)O layer. Possible applications and future experiments of the method inserting isotopic markers such as D in functional layers of chalcopyrite‐type thin‐film solar cells and beyond are discussed. Abstract : This contribution describes an approach to introduce deuterium (D) as an isotopic marker into solution‐grown buffer layers CdS and Zn(O, S) for Cu(In, Ga)Se2 (CIGS) thin‐film solar cells. The D content has no detrimental effect on the performance of the CIGS cells. Depth profiles obtained by time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) confirm the incorporation of D within the Zn(O, S) layer.